How can healthcare professionals better support family caregivers in the final days of life: Could the “Family’s Voice Diary” help? A qualitative study based in an area of high socio-economic deprivation - Donna Wakefield; Zoe Booth; Michaela Fay; Matthew Breckons (Palliative Care and Social Practice)
Background: Family caregivers play a vital role in supporting patients at the end of life, a role that can impact their own well-being. Healthcare professionals may feel unprepared to support caregivers. The Family’s Voice Diary (FVD) was co-developed with bereaved carers and a wide range of healthcare professionals as a tool to improve caregiver support. Objectives: To understand challenges carers face in receiving support and whether the FVD has the potential to improve this. Design: Qualitative interviews with thematic analysis. Methods: Family’s Voice Diaries were provided to hospital, hospice and community nursing teams, to be offered to carers when a patient was in their final days of life. Each diary invited carers to return the diary if they wished to volunteer for an interview and/or consent to analysis of the content of their completed FVD. Adverts were circulated inviting healthcare professionals to interview. Results: n  = 23 diaries were returned, which included written reflections and notes used as an aide memoire to discuss with healthcare professionals. Qualitative interviews were conducted with n  = 6 healthcare professionals and n  = 1 bereaved carer. Main themes included the carer’s reluctance to ask for support and healthcare professionals feeling unprepared to discuss dying. Using the diary as a communication aid to build a collaborative relationship with staff was valued. Barriers to implementation included a lack of understanding of the purpose of the diary. Conclusion: This study adds to the evidence base that there is a need for further carer support and clearer communication at the end of life. The diary appears to be valued as an optional addition to prompt communication, aid self-reflection and signpost to further support. Clearer instruction/training on the purpose of the diary could improve its implementation. Further training for healthcare staff, to enable them to feel more comfortable discussing dying with carers and be able to offer support, would be beneficial.